1996
DOI: 10.1007/bf02249608
|View full text |Cite
|
Sign up to set email alerts
|

Using the Steers-Rhodes (1984) framework to identify correlates of employee lateness

Abstract: ABSTRACT'. Based on a sample of factory workers, this field study examined correlates of employee lateness. The framework provided by Steers and Rhodes (1984) was used to identify variables related to voluntary and involuntary lateness. Both motivation and ability to be o.n time were found to be important determinants of lateness as well as joint moderators in explaining lateness. The negative job satisfaction-lateness relationship suggested that a proportion of lateness behavior represented a response to an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Though this research has produced sometimes‐conflicting findings and the overall explanatory power of job satisfaction has been widely debated over that time, it has been generally accepted in the workplace literature that satisfied workers are more productive and perform at a higher level (Schleicher et al , 2004; Harter et al , 2002; Judge et al , 2001; Sousa‐Pouza and Sousa‐Pouza, 2000). It has further been demonstrated that low‐job satisfaction can lead to higher absenteeism and turnover (Clark et al , 2005; Johns, 2002; Bardsley and Rhodes, 1996; Dwyer and Ganster, 1991; Leigh and Lust, 1988; Adler and Golan, 1981; Ronan, 1970; Vroom, 1964). Additionally, a wide body of work and health research has shown the link between job satisfaction and worker health (Karasek, 1979; Totterdell et al , 2006; Tsutsumi, 2005).…”
Section: Job Quality Characteristics and Job Satisfaction Overviewmentioning
confidence: 99%
“…Though this research has produced sometimes‐conflicting findings and the overall explanatory power of job satisfaction has been widely debated over that time, it has been generally accepted in the workplace literature that satisfied workers are more productive and perform at a higher level (Schleicher et al , 2004; Harter et al , 2002; Judge et al , 2001; Sousa‐Pouza and Sousa‐Pouza, 2000). It has further been demonstrated that low‐job satisfaction can lead to higher absenteeism and turnover (Clark et al , 2005; Johns, 2002; Bardsley and Rhodes, 1996; Dwyer and Ganster, 1991; Leigh and Lust, 1988; Adler and Golan, 1981; Ronan, 1970; Vroom, 1964). Additionally, a wide body of work and health research has shown the link between job satisfaction and worker health (Karasek, 1979; Totterdell et al , 2006; Tsutsumi, 2005).…”
Section: Job Quality Characteristics and Job Satisfaction Overviewmentioning
confidence: 99%
“…Some factors ended in tardiness is predicted by commuting, family issues over the work, personality, and commitment to the company [1]- [3]. Both in the organization and studies, lateness has a little highlight compared to other behaviors [2] [4]. Absenteeism and turnover are distinguishable whereas the lateness is possibly not present in employee records [2].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it been shown that satisfied workers are more productive and perform at a higher level (Schleicher, Watt & Greguras, 2004;Harter, Schmidt & Hayes, 2002;Judge et al, 2001;Souza-Poza & Souza-Poza, 2000;Westover, 2010a). On the other hand, low job satisfaction reportedly leads to higher absenteeism and turnover (Clark, Peters, and Tomlinson, 2005;Bardsley and Rhodes, 1996;Dwyer and Ganster, 1991;Leigh and Lust, 1988;Adler and Golan, 1981;Ronan, 1970;Vroom, 1964).…”
Section: Introductionmentioning
confidence: 99%